Solidarity in the Age of Globalization: Approaches from the Philosophy for Peace - Jalali-Rabbani, Martha (Convergencia Revista de Ciencias Sociales; Vol. 27 (2020)DO - 10.29101/crcs.v27i0.12439, 2019)
This article approaches the challenges to solidarity in the age of globalization in terms of the limitations set to it by a) the structure and values of global capitalism, b) political membership to the Nation-State, and c) membership to cultural groups that do not allow self-reflection, learning and changing. Building on Martínez Guzmán´s Philosophy for Peace, the political self from the perspective of our human competences to extend solidarity to strangers are redefined, more specifically, a) our capacity to communicate and understand each other, b) our capacity to recognize sameness in each other, c) our capacity to cooperate. At the end, this revised understanding of the self is applied to identify the political institutional changes that are necessary for the extension of solidarity: a) a transnational public sphere, b) global domestic politics, and c) a constitution for the world society.